A case of recurrent status epilepticus and successful management with progesterone. Issue 1 (March 2016) - Ramanujam, Bhargavi; Arora, Amit; Malhotra, Varun; Dash, Deepa; Mehta, Santosh; Tripathi, Manjari
Abstract: Catamenial epilepsy (CE) is a commonly observed phenomenon among women with epilepsy, the management of which is both hormonal and non‐hormonal. Progesterone therapy has been tried in these patients, as the possible mechanism of CE is withdrawal of progesterone and a higher oestrogen/progesterone ratio in the perimenstrual and periovulatory periods. Here, we describe a 24‐year‐old lady with multiple seizure types since childhood, which were refractory to adequate antiepileptic drug therapy after menarche with catamenial clustering of seizures. She went on to have several episodes of non‐convulsive status epilepticus also with similar periodicity, which would abate only with midazolam infusion, without the need for ventilatory support. She was tried on acetazolamide, progesterone vaginal pessaries, and maximum tolerated doses of antiepileptic medications, but finally responded to intramuscular and oral progesterone, and has been seizure‐free for more than a year.